Fixational saccade inhibition and pupil dilation during self-paced limb movement preparation - Jan W. Brascamp; Bobicheng Zhang; Vasili Marshev (PLoS ONE, 2025)
Fixational saccades are modulated in anticipation of several kinds of stimuli and motor actions, suggesting that they can form an overt marker of preparatory state. However, no existing work has studied fixational saccades ahead of spontaneous limb movements in the absence of sensory stimuli, in order to isolate motor preparation from other anticipatory processes (e.g., those related to stimulus processing). Here we examined fixational saccades while participants made self-paced hand and foot movements. We observed that fixational saccade rate steadily dropped prior to either kind of motor action, and recovered immediately after. To examine the relation between this fixational saccade rate signal and other known signals that precede volitional action, we analyzed how this signal related to anticipatory pupil size changes in the same dataset. Replicating previous work, we found steady pupil dilation ahead of limb movements, followed by rapid re-constriction. The amplitude of this pupil signal covaried across individual limb movements with that of the fixational saccade rate signal. The pupil modulations, moreover, followed too shortly after the accompanying fixational saccade rate modulations to be caused by saccade-induced changes in visual input. Together, these observations suggest a joint neural factor influencing both fixational saccade rate and pupil size ahead of limb movements. We discuss possible interpretations of our findings, both specific ones that center on processes of motor planning or temporal expectation, and more general ones that are in terms effort.